Risk management in Business Activity – selected issues - Przesmycka, Agnieszka; Podstawka, Marian (Management and Administration Journal, 2023)
The purpose of this paper is to present the impact of risk on the business activity of enterprises and the areas which ought to be subject to risk management.The efficient management of an enterprise is necessarily connected with risk management. Decisions taken in an enterprise are meant to bring about particular consequences in the future, wherefore they always bear certain risk. In the current economic conditions, the management staff is forced to take into consideration the enterprise’s  exposure to risk when taking strategic decisions. The enterprise management system must be integrated with a risk management system at every stage. This coordination begins at the level of planning already and ends at the stage of control. Management is namely ever more frequently identified with the security of a business, which involves reducing risk.